The role of regulation in geothermal energy in the UK. (February 2023) - McClean, A.; Pedersen, O.W.
Abstract: Geothermal energy is a constant, reliable source of energy which has the potential to play a key role in decarbonisation of the heating of buildings in the UK. At present it is underutilized, making up just 4.5 per cent of renewable energy used in the UK, and a significant reason for this is the lack of clear regulatory framework for addressing the environmental impacts and supporting private investment. This article identifies the environmental and financial risks of both shallow and deep geothermal energy and analyses if, how, and to what extent they are addressed in the current regulatory regime. It finds that regulation of the environmental impacts is piecemeal and recommends reform of the regulatory regime to cover all geothermal energy systems and operations. This article also finds that the current regulatory framework fails to address the significant upfront costs of both shallow and deep geothermal energy operations or the potential for depletion of the geothermal resource on which they depend. It highlights the need for a regulatory regime that protects geothermal energy resources from overabstraction and balances the interests of multiple users, and for financial incentives to encourage growth of both the shallow and deep geothermal energy industries. Highlights: Provides the first in-depth analysis of the regulatory regime applicable to geothermal energy. The regulation of environmental impacts of geothermal energy is piecemeal. Reform of the environmental permitting regime is one option to address this. A regime for the sharing of information would reduce the financial risks. Financial incentives are also required to address the high up-front costs.